PENCAPAIAN PERTUMBUHAN LINEAR DAN STATUS PUBERTAS REMAJA DENGAN RIWAYAT GIZI BURUK PADA USIA DINI - Amelia Amelia; Sri Muljati; Dyah Santi Puspitasari (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2010)
Background: The second growth spurt of human life cycle occured during adolescence. Among malnourished children, growth spurt on linear growth could be happened if supported by a better environment and prolong of physical growth. While the failure of catch up on linear growth due to continued residence in the same environment as they malnourished. Almost all of those who diagnosed as severely malnourished were categorized as stunted too. Objectives: The aimed of the study is to analyze linear growth attaintment as well as the puberty status among adolescence who suffered from severe malnutrition at early age. Methods: A cross sectional design was implemented in the study. Subjects were adolescence aged 10 - 17 years who ever admitted to Nutrition Clinic at Center of Food and Nutrition Research and Development Bogor at the age of under-three years. Data collected including weight and height, health and puberty status as well as socio economic data. As the comparison, match for sex and age, healthy and wellnourished teenage were also recruted from the same home residence. The data were analyzed to determine linear growth attaintment of the subjects, and paired samples test were calculated using SPSS. Results: Catch up growth occurred among 32.3% of teenage boy and 23.4% of teenage girls. Mean Height for Age z-scor among the subjects is -2.32 ± 0.8 compared to -1.18 ± 0.59 among comparison group. There was a significant difference on height for age z-score among subjects at adolesence compared to at under-three of aged at all age group. No difference on linear growth attaintment at adolesence based on degree of severity of stunting at the age of under-three. There was also no difference on mother's height among teenage based on height for age category (p>0.05). Age of menarche among teenage girl subjects was 13.03 ± 1.25 years while in comparison girls was 12.55 ± 1.10 years (p>0.05). For teenage boy, 'wet dream' occurred at 14.02 ± 1.19 years as compared to 13.63 ± 1.77 years for the comparison group. Conclusions: Catch up on linear growth only determined among some of the subjects. No difference on linear growth attaintment at adolesence based on degree severity of stunting at the age of under-three.   Keywords: severe malnutrition, stunting, linear growth, adolesence. puberty